2019
DOI: 10.3390/molecules24061162
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-Substituted 3-Arylquinoline Derivatives as Potential Anti-Inflammatory Agents Through Inhibition of LPS-Induced Inflammatory Responses in Macrophages

Abstract: We describe herein the preparation of certain 2-substituted 3-arylquinoline derivatives and the evaluation of their anti-inflammatory effects in LPS-activated murine J774A.1 macrophage cells. Among these newly synthesized 2-substituted 3-arylquinoline derivatives, 2-(4-methoxy- benzoyl)-3-(3,4,5-trimethoxyphenyl)quinoline (18a) and 2-(4-fluorobenzoyl)-3-(3,4,5-trimethoxy- phenyl)quinoline (18b) are two of the most active compounds which can inhibit the production of NO at non-cytotoxic concentrations. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Among the compounds, 63a and 63b ( Figure 8 ) were the most active and they could inhibit production of NO at non-cytotoxic concentrations. Moreover, the two compounds had significant anti-inflammatory activities on LPS-activated macrophages through inhibiting production of NO, TNF-α, and IL-6, attenuating the activity of NF-êB, repressing iNOS expression, and suppressing phosphorylation of MAPKs 78 .…”
Section: Recent Development In Anti-inflammatory Agentsmentioning
confidence: 99%
“…Among the compounds, 63a and 63b ( Figure 8 ) were the most active and they could inhibit production of NO at non-cytotoxic concentrations. Moreover, the two compounds had significant anti-inflammatory activities on LPS-activated macrophages through inhibiting production of NO, TNF-α, and IL-6, attenuating the activity of NF-êB, repressing iNOS expression, and suppressing phosphorylation of MAPKs 78 .…”
Section: Recent Development In Anti-inflammatory Agentsmentioning
confidence: 99%
“…This interaction is favored by the formation of hydrogen bonds with Ala 275, Tyr 284, and NAG 404 residues and hydrophobic bonds with Asn 161, Trp 220, Arg 274, Ala 275, Tyr 276, Tyr 284, and NAG 404 residues. Previous studies showed that some quinoline derivatives with anti-inflammatory properties might form a stable complex with TNF α by docking in the middle pocket of dimers [ 36 ]⁠. However, no hydrogen bond was observed in these studies which could be explained by the different nature of the docked molecule and the docking approach.…”
Section: Discussionmentioning
confidence: 87%
“…Orange solid; yield: 70%; Mp. 139.8-140.2 °C ([ 22 ], lit: 138.1-139.2 °C); 1 H-NMR (CDCl 3 ) δ 10.18 (s, 1H, CHO), 8.32-8.26 (m, 2H), 8.09 (s, 1H, 3-H), 7.91-7.87 (m, 1H), 7.82-7.77 (m, 1H); 13 C-NMR (CDCl 3 ) δ 192.56, 152.34, 148.67, 144.20, 131.30, 130.85, 130.19, 128.05, 124.41, 117.57.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have synthesized certain 2-substituted 3-arylquinoline derivatives and the evaluation of their anti-inflammatory effects in LPS-activated murine macrophage cell line J774A.1 cells. 2-(4-Fluoro-benzoyl)-3-(3,4,5-trimethoxyphenyl)quinoline significantly decreases the secretion of pro-inflammatory cytokines (TNF-α and IL-6) in the LPS-activated macrophages [ 22 ]. The present report describes the synthesis of novel hybrid molecules, which bears both quinoline and chalcone moieties and evaluate for their NRF2 activating activities.…”
Section: Introductionmentioning
confidence: 99%